2002
DOI: 10.1038/sj.bjc.6600258
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of mitomycin C, cisplatin and continuous infusion 5-fluorouracil (MCF) in the treatment of patients with carcinoma of unknown primary site

Abstract: Newcastle-upon-Tyne NE1, UK Carcinoma of unknown primary site remains a common clinical diagnosis, accounting for between 5 and 10% of all cancer patients. Numerous combination chemotherapy regimens have been used in the management of carcinoma of unknown primary site, resulting in response rates of 0 -48%. We present the results of a single centre phase II study of the use of the combination of mitomycin C (7 mg m 72 on day 1 of cycles 1, 3 and 5) cisplatin (60 mg m 72 on day 1) and continuous infusion 5-fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There was one consecutive case series study (Gill et al , 1991) and the other 23 studies were single arm clinical trials (Raber et al , 1991; Briasoulis et al , 1998, 2000, 2008; Parnis et al , 2000; Greco et al , 2001, 2002; Guardiola et al , 2001; Macdonald et al , 2002; Balana et al , 2003; Mukai et al , 2003, 2010; Park et al , 2004; Piga et al , 2004; Pouessel et al , 2004; El-Rayes et al , 2005; Pittman et al , 2006; Schneider et al , 2007; Pentheroudakis et al , 2008; Hainsworth et al , 2009; Schuette et al , 2009; Yonemori et al , 2009; Moller et al , 2010). Three trials (Briasoulis et al , 1998, 2000; Pentheroudakis et al , 2008) also involved a small proportion of favourable CUP patients in their studies, and we extracted the data only from the unfavourable subset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was one consecutive case series study (Gill et al , 1991) and the other 23 studies were single arm clinical trials (Raber et al , 1991; Briasoulis et al , 1998, 2000, 2008; Parnis et al , 2000; Greco et al , 2001, 2002; Guardiola et al , 2001; Macdonald et al , 2002; Balana et al , 2003; Mukai et al , 2003, 2010; Park et al , 2004; Piga et al , 2004; Pouessel et al , 2004; El-Rayes et al , 2005; Pittman et al , 2006; Schneider et al , 2007; Pentheroudakis et al , 2008; Hainsworth et al , 2009; Schuette et al , 2009; Yonemori et al , 2009; Moller et al , 2010). Three trials (Briasoulis et al , 1998, 2000; Pentheroudakis et al , 2008) also involved a small proportion of favourable CUP patients in their studies, and we extracted the data only from the unfavourable subset.…”
Section: Resultsmentioning
confidence: 99%
“…Two independent reviewers evaluated the responses, which were the primary outcome of the study in only two studies (Culine et al , 2003; Moller et al , 2010). In all, 14 studies reported prospective calculation of the study size (Greco et al , 2002; Macdonald et al , 2002; Pouessel et al , 2004; El-Rayes et al , 2005; Palmeri et al , 2006; Pittman et al , 2006; Schneider et al , 2007; Pentheroudakis et al , 2008; Hainsworth et al , 2009, 2010; Huebner et al , 2009; Schuette et al , 2009; Yonemori et al , 2009; Mukai et al , 2010). Among the RCTs, only one study had a clear description of the method of allocation concealment (Assersohn et al , 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents all existing randomized trials specifically studying CUP patients, with the regimens and their respective median overall survival and response rates when available [11,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. As described, the prognostic classification (based on performance status and LDH levels) separates a favourable prognosis subgroup (median survival of 12 months) from a poor prognosis subgroup (median survival of 4 months); for the latter, best supportive care should also be considered upfront in the management algorithm [3,13].…”
Section: One-size Fits All Approachmentioning
confidence: 99%
“…Thirty-four regimens were administered as first-line treatment in 1,380 patients. Under front-line regimen, the overall ORR was 430/1,380 (31%, [27][28][29][30][31][32][33]) and the non-progression rate was 731/1,206 (60% [57-63]). The median overall survival was 8 months and the progression-free survival was 4.2 months.…”
Section: Front-line Regimensmentioning
confidence: 99%